Studi Literatur : Faktor-Faktor Beban Kerja Yang Mempengaruhi Stres Kerja Anggota Polisi - Salsabila Putri Azzahra; Anis Masyitoh Ngabidah; Alifah Tsabita Fathin; Mic Finanto Ario Bangun (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This study aims to gather information about what workload factors have an impact on the work stress of police officers. The research method used is a literature study, where several previous studies are collected and reviewed in more depth to find out about what workload factors affect work stress in police officers. The results of this study indicate that workload has an impact on work stress. Workload itself can be divided into two categories, namely quantitative and qualitative workload. Quantitative workload includes aspects such as working hours, volume of work, and the quality of the difficulty of the work carried out. Meanwhile, qualitative workload is related to the individual's ability to complete tasks well and the individual's perception of the workload faced. This is reinforced by research results from previous studies which indicate that there is a relationship between workload and job stress. It is hoped that the results of this study can provide a more comprehensive perception of how workload affects work stress in police officers, and become the basis for developing better stress management strategies in the police work environment.